Analysis of service quality and customer satisfaction at the Sky Lounge And Cafe padang state university hotel padang - Reynaldy Reynaldy; Kasmita Kasmita; Wiwik Gusnita; Rahmi Holinesti (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
Sky Lounge and Café at UNP Hotel Padang is a culinary service business unit with a modern concept and exclusive services. Maintaining and improving service quality remains a strategic challenge, as it directly impacts customer satisfaction and loyalty. This study analyzes consumer perceptions of service quality and its effect on satisfaction using a quantitative approach, with 100 respondents selected through accidental sampling. The results show that all service quality dimensions (tangibles, reliability, responsiveness, assurance, empathy) were rated in the "good" category, with scores ranging from 3.0 to 3.4. Among these, tangibles (3.4) and assurance (3.3) were the highest-rated dimensions, while responsiveness (2.8) was identified as the weakest aspect requiring improvement. The study further reveals that service quality has a significant positive effect on customer satisfaction, accounting for 55.1% of its variance. The findings suggest that targeted improvements in responsiveness and empathy are crucial for enhancing overall customer satisfaction and loyalty. This research provides practical recommendations for service enhancement in the hospitality sector, particularly in competitive urban settings.